Zearalenone Mycotoxicosis: Pathophysiology and Immunotoxicity - Assumaidaee, Ajwad A. M.; Ali, Nathera M.; Ahmed, Shahad W. (The Iraqi Journal of Veterinary Medicine, 2020)
Mycotoxicosis refers to the deleterious pathological effects of different types of toxins produced by some worldwide distributing fungi. Mycotoxins, as secondary metabolites are affecting different organs and systems both in animals and human beings. Zearalenone (ZEA), the well-known estrogenic mycotoxins, is an immunotoxic agent. This macrocyclic beta-resorcyclic acid lactone is mycotoxin procreated as a secondary metabolic byproduct by several types of Fusarium, encompassing Fusarium roseum, Fusarium culmorum, Fusarium graminearum, and different other types. Attributing to its potent estrogenic activity, ZEA has been incriminated as one of the major causes of female reproductive disorders. Thus, the purpose of the present review article is to appraise the pathophysiological consequences and subsequent explore the progress in the research field of zearalenone immunotoxicities.